Lie group analysis of heat flux effect on MHD second slip flow for a slightly rarefied gas past a stretching sheet with heat generation - Megahed, Ahmed M.; Abdel-Rahman, Reda G. (Technical Sciences, 2019)
The present paper discusses steady MHD second order slip flow and heat transfer for a slightly rarefied gas due to an impermeable stretching sheet with heat flux and internal heat generation. By using the Lie group analysis, new similarity transformations are obtained. Employing these transformations, allows the partial differential equations governing the problem to transform into a system of ordinary differential equations which are later treated numerically using shooting method. Effects of the governing parameters on the dimensionless velocity and dimensionless temperature profiles are outlined graphically. Furthermore, results for the local skin-friction coefficient and the local Nusselt number are presented for some different values of the governing parameters in a tabular form. Also, results show that there is a strong dependency of the dimensionless temperature on the heat flux.